Combustion mechanism of propane-air swirling premixed flame near lean flammability limit - Yuyang JIANG; Makihito NISHIOKA (Journal of Thermal Science and Technology, 2025)
This study investigated a premixed propane-air flame in a partially tapered swirl burner. Experimentally, we found that a flame resembling a morning glory flower formed at an equivalence ratio near the lean flammability limit. A numerical simulation of the flame with detailed chemistry revealed that the upstream flame tip existing at the central axis in the recirculation zone was significantly weakened, whereas the curved flame convex downstream was significantly strengthened. In addition, high peaks of temperature, heat release rate (HRR), and concentrations of OH, O, and H radicals were formed immediately behind the latter curved flame, which enabled the flame to exist stably under conditions very close to the lean flammability limit. Subsequently, to identify the influence of the Lewis number on the flame shape, adiabatic methane-air swirling flames were simulated with the Lewis numbers manipulated between 0.90 and 1.20. The results show that an increase in the Lewis number from unity changes the flame shape from a circular paraboloid to one somewhat similar to a morning-glory flower, whereas a decrease in the Lewis number from unity changes the flame shape from a circular paraboloid to one somewhat similar to a comet. This result suggests that the large difference in flame shapes among hydrogen-air, methane-air, and propane-air under very lean conditions is due to the difference in their Lewis numbers.